Low power low-dropout (LDO) regulator for wireless sensor node (WSN) - Puspitasari, Astra (2015)
The purpose of this report is to highlight the results of the project which is to create a Low Power Low Dropout (LDO) regulator for Wireless Sensor Node In this project, a low power LDO has to be designed using 0.18µm CMOS technology. The input supply voltage will be 1.2V and the output has to be regulated at 1V for the digital circuits with an output current of 1mA. The LDO consume a very small quiescent current of 6.46µA and power of 7.75 µW and exhibit a low temperature coefficient of 74 ppm/ ºC under full load condition. The circuit is in sub-threshold mode to achieve low power consumption. In this project, simulation is conducted to sweep the temperature in the range of -40ºC to 120ºC to ensure the proposed circuits to work in the output range even under extreme temperature condition. The LDO is design to achieve small area and low complexity.